A manganese-based three-layer core-shell structure positive electrode material for sodium ion batteries

The Cu-doped manganese-based three-layer core-shell structure positive electrode material was prepared by spray pyrolysis, which solved the electrolyte decomposition and material damage caused by the formation of Ni4+ during the charging and discharging process of NaNimFenMn1-m-nO2 material, and achieved the battery capacity Improved stability and cycle stability.

CN117577796BActive Publication Date: 2025-02-07JIANGSU HAONA NEW ENERGY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311388813.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-24
Publication Date
2025-02-07
Estimated Expiration
2043-10-24

AI Technical Summary

Technical Problem

Ni4+ is formed on the surface of the NaNimFenMn1-m-nO2 material during charging and discharging, resulting in side reactions with the electrolyte, causing electrolyte decomposition and damage to the crystal structure of the material, thereby rapidly attenuating the battery life.

Method used

The Cu-doped manganese-based three-layer core-shell structure positive electrode material (NaNixCuyFezMn1-x-y-zO2) was prepared by spray pyrolysis. By adjusting the ionic components in the mixed solution, the gradient distribution of the chemical composition of each layer of the material is realized and the material interface is improved. and internal electrochemical properties.

Benefits of technology

It effectively reduces the attenuation of battery capacity, significantly improves circulation stability, and improves material surface stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004511696070000081
    Figure BDA0004511696070000081
  • Figure BDA0004511696070000091
    Figure BDA0004511696070000091
Patent Text Reader

Abstract

The present invention relates to the technical field of sodium ion batteries, and specifically to a manganese-based three-layer core-shell structure positive electrode material for sodium ion batteries, which takes into account high specific capacity, high stability and low cost. First, three metal mixed salt solutions with gradient differences in stoichiometric ratios are prepared, and then the three metal salt solutions are ionized by an ultrasonic atomizer and sprayed into a reaction device in sequence, and a three-layer core-shell structure precursor material is generated in the form of nucleation, crystallization and high-temperature pyrolysis, and further uniformly mixed and then sintered to obtain a manganese-based three-layer core-shell structure positive electrode material. Compared with the traditional sodium ion battery layered oxide positive electrode material with uniform components, the present invention can effectively control the chemical composition of the microscopic components of the material, and achieve the regulation of the specific element ratio in the microscopic part of the material, which can accurately improve the performance of the material, reduce the attenuation of the material capacity, and improve the electrochemical performance and cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a manganese-based three-layer core-shell structure positive electrode material for sodium ion batteries. Background Art

[0002] Currently, sodium-ion batteries have entered the early stages of commercialization. Cathode materials are key materials that determine the performance of sodium batteries. Cathode materials with high energy density, long cycle life, and high safety have become the research and development focus of sodium-ion batteries.

[0003] At present, sodium ion battery layered sodium nickel iron manganese oxide (NaNi m Fe n Mn 1-m-n O2) type positive electrode materials have been commercialized. They have the advantages of high specific capacity, low cost and good safety. They are one of the most promising positive electrode materials for the development of sodium ion batteries. The Ni in the sodium nickel iron manganese oxide positive electrode material mainly contributes to the capacity, Mn plays a role in supporting the structural stability of the material, and Fe mainly plays a synergistic role between Ni and Mn. However, NaNi m Fe n Mn 1-m-n During the charge and discharge process of O2 material, Ni 4 + , high-valent Ni 4+ It will produce side reactions with the electrolyte, causing the electrolyte to decompose and damage the crystal structure of the surface material, ultimately causing the battery life to decay rapidly. Summary of the invention

[0004] The technical problem to be solved by the present invention is: NaNi m Fe n Mn 1-m-n During the charge and discharge process of O2 material, Ni 4+ , high-valent Ni 4+ The side reaction with the electrolyte will cause the electrolyte to decompose and damage the crystal structure of the surface material, which will eventually cause the battery life to decay rapidly. The present invention adopts the method of spray pyrolysis to prepare the Cu-doped manganese-based three-layer core-shell structure positive electrode material (NaNi x Cu y Fe z Mn 1-x-y-z O2), can accurately control the chemical composition of the material from the core to the surface, accurately improve the material interface and internal electrochemical properties, thereby effectively reducing the attenuation of battery capacity and improving cycle stability.

[0005] To achieve the above object, the present invention provides the following technical solution: A manganese-based three-layer core-shell structure positive electrode material for sodium ion battery, which has the following molecular formula: NaNix Cu y Fe z Mn 1-x-y-z O2, the positive electrode material is a three-layer structure consisting of an inner layer, a middle layer and an outer layer, and the stoichiometric ratio of Na, Ni, Cu, Fe and Mn in each layer is 0.5-4:x:y:z:(1-xyz), wherein 0<x≤0.4, 0<y≤0.2, 0<z<0.6; and the content of Ni in each layer decreases from the inside to the outside, and the content of Mn in each layer increases from the inside to the outside.

[0006] Preferably, in the inner layer, the molar ratio of Na, Ni, Cu, Fe and Mn is 1.03:0.25-0.45:0.05-0.15:0.2-0.4:0.2-0.3; in the middle layer, the molar ratio of Na, Ni, Cu, Fe and Mn is 1.03:0.15-0.25:0.05-0.15:0.2-0.4:0.25-0.4; in the outer layer, the molar ratio of Na, Ni, Cu, Fe and Mn is 1.03:0.05-0.15:0.05-0.15:0.2-0.4:0.45-0.65.

[0007] Preferably, the method for preparing the above-mentioned manganese-based three-layer core-shell structure positive electrode material for sodium ion battery comprises the following steps:

[0008] S1: Sodium salt, nickel salt, iron salt, manganese salt and copper salt are weighed and dissolved in deionized water according to different stoichiometric ratios to prepare mixed solutions A, B and C; the content of Ni in the mixed solutions A, B and C decreases gradually, and the content of Mn in the mixed solutions A, B and C increases gradually;

[0009] S2: ionizing the mixed solution A, spraying it into the reaction device, evaporating and precipitating it, and then pyrolyzing it to generate the precursor A; ionizing the mixed solution B, spraying it into the reaction device, and using the carrier gas to disperse and suspend the precursor A in the reaction device to form a coating layer covering the precursor A, and pyrolyzing it to obtain two layers of precursor B; ionizing the mixed solution C, spraying it into the reaction device, and using the carrier gas to disperse and suspend the two layers of precursor B in the reaction device to form a coating layer covering the precursor B, and pyrolyzing it to obtain three layers of precursor C;

[0010] S3: The three-layer precursor C is pre-sintered, crushed, sintered and then pulverized to obtain a manganese-based three-layer core-shell structure positive electrode material.

[0011] Preferably, the sodium salt, nickel salt, iron salt, manganese salt and copper salt refer to acetates of these metals, the ionization device is an ultrasonic atomizer, and the pyrolysis temperature is 400-600°C.

[0012] Preferably, the mass ratio of mixed solution A, mixed solution B, and mixed solution C is 3-7:2-6:1-5, and the concentration of the solute in mixed solution A, mixed solution B, and mixed solution C is 10-30wt%.

[0013] Preferably, the pre-calcination temperature is 350-500° C. and the pre-calcination time is 4-7 hours.

[0014] Preferably, the crushing device is a double-roller machine, and the gap between the double-roller crushing is 0.05-2mm.

[0015] Preferably, the sintering temperature is 700-950° C. and the sintering time is 6-15 hours.

[0016] A sodium ion battery positive electrode, the battery positive electrode comprising the manganese-based three-layer core-shell structure positive electrode material for the sodium ion battery.

[0017] A manganese-based three-layer core-shell structure positive electrode material for a sodium ion battery is used in the preparation of a positive electrode for a sodium ion battery.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The present invention forms a nickel-copper-iron-manganese-sodium positive electrode material with a three-layer core-shell structure by spray pyrolysis and layered crystallization coating of the solution. By adjusting the ion components in the mixed solution A, B, and C, the chemical components of each shell layer of the material particles from the inside to the outside are controlled. Various metal salts can form a uniform mixture at the molecular level in the solution, so that the composition distribution of each layer is uniform, and the morphology and particle size of the obtained powder are uniform.

[0020] (2) In the manganese-based three-layer core-shell structure positive electrode material prepared by the present invention, the nickel content gradually decreases from the inner layer to the outer layer, and the Mn content gradually increases. At the same time, the incorporation of Cu can synergistically stabilize the Ni and Fe atoms, thereby ensuring a higher capacity of the material and significantly improving the surface stability of the material. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Example 1

[0023] Sodium acetate, nickel acetate, copper acetate, iron acetate and manganese acetate were weighed respectively and dissolved in deionized water, the mass of deionized water being 5 times the sum of the masses of each component, and stirred and heated to 70° C. until completely dissolved to obtain mixed solution A, mixed solution B and mixed solution C, so that the molar ratio of Na, Ni, Cu, Fe and Mn in mixed solution A was 1.03:0.3:0.1:0.3:0.3; the molar ratio of Na, Ni, Cu, Fe and Mn in mixed solution B was 1.03:0.2:0.1:0.35:0.35; the molar ratio of Na, Ni, Cu, Fe and Mn in mixed solution C was 1.03:0.1:0.1:0.2:0.6; the mass ratio of mixed solution A, mixed solution B and mixed solution C was 5:4:3;

[0024] The mixed solution A is ionized by an ultrasonic atomizer and then sprayed into a reaction device. During the gradual heating process, the water content of the atomized droplets evaporates to form a solid precipitate, which is further pyrolyzed at 450°C to generate a precursor A. The tail gas in the device after the reaction is completely removed by vacuum pumping, and then nitrogen is introduced into the reaction device to disperse and suspend the precursor A in the device. The mixed solution B is ionized by an ultrasonic atomizer and sprayed into the reaction device to form suspended droplets covering the precursor A. The water content of the droplets evaporates to form a crystalline coating layer, which is further pyrolyzed at 460°C to obtain a two-layer precursor B. The tail gas in the device after the reaction is completely removed by vacuum pumping. Then, nitrogen is introduced into the reaction device to disperse and suspend the two-layer precursor B in the device, and then the mixed solution C is ionized by an ultrasonic sprayer and sprayed into the reaction device to form suspended droplets covering the two-layer precursor B. After the water in the droplets evaporates, a crystalline coating layer is formed on its surface, which is further pyrolyzed at 470°C to obtain a three-layer precursor C; the three-layer precursor C is placed in an atmosphere box furnace, pre-burned at 500°C for 4h, the gap between the rollers is set to 0.5mm, and crushed with a mechanical roller, and then placed in an atmosphere sintering furnace, sintered at 900°C for 12h, and crushed with an air flow mill after sintering to obtain a manganese-based three-layer core-shell structure positive electrode material Na 1.03 Ni 0.2 Cu 0.1 Fe 0.28 Mn 0.42 O2.

[0025] Example 2

[0026] Sodium acetate, nickel acetate, copper acetate, iron acetate and manganese acetate were weighed respectively and dissolved in deionized water, the mass of deionized water being 5 times the sum of the masses of each component, and stirred and heated to 70° C. until completely dissolved to obtain mixed solution A, mixed solution B and mixed solution C, so that the molar ratio of Na, Ni, Cu, Fe and Mn in mixed solution A was 1.03:0.4:0.1:0.3:0.2; the molar ratio of Na, Ni, Cu, Fe and Mn in mixed solution B was 1.03:0.2:0.2:0.3:0.3; the molar ratio of Na, Ni, Cu, Fe and Mn in mixed solution C was 1.03:0.1:0.2:0.2:0.5; the mass ratio of mixed solution A, mixed solution B and mixed solution C was 5:4:3;

[0027] The mixed solution A is ionized by an ultrasonic atomizer and then sprayed into a reaction device. During the gradual heating process, the water content of the atomized droplets evaporates to form a solid precipitate, which is further pyrolyzed at 400°C to generate a precursor A. The tail gas in the device after the reaction is completely removed by vacuum pumping, and then nitrogen is introduced into the reaction device to disperse and suspend the precursor A in the device. The mixed solution B is ionized by an ultrasonic atomizer and sprayed into the reaction device to form suspended droplets covering the precursor A. The water content of the droplets evaporates to form a crystalline coating layer, which is further pyrolyzed at 470°C to obtain a two-layer precursor B. The tail gas in the device after the reaction is completely removed by vacuum pumping. Then, nitrogen is introduced into the reaction device to disperse and suspend the two-layer precursor B in the device, and then the mixed solution C is ionized by an ultrasonic sprayer and sprayed into the reaction device to form suspended droplets covering the two-layer precursor B. After the water in the droplets evaporates, a crystalline coating layer is formed on its surface, which is further pyrolyzed at 480°C to obtain a three-layer precursor C; the three-layer precursor C is placed in an atmosphere box furnace, pre-burned at 450°C for 4h, the gap between the rollers is set to 0.5mm, and crushed with a mechanical roller, and then placed in an atmosphere sintering furnace, sintered at 920°C for 10h, and crushed with an air flow mill after sintering to obtain a manganese-based three-layer core-shell structure positive electrode material Na 1.03 Ni 0.23 Cu 0.17 Fe 0.27 Mn 0.33 O2.

[0028] Example 3

[0029] Sodium acetate, nickel acetate, copper acetate, iron acetate and manganese acetate were weighed respectively and dissolved in deionized water, the mass of deionized water being 5 times the sum of the masses of each component, and stirred and heated to 75° C. until completely dissolved to obtain mixed solution A, mixed solution B and mixed solution C, so that the molar ratio of Na, Ni, Cu, Fe and Mn in mixed solution A was 1.03:0.4:0.1:0.25:0.25; the molar ratio of Na, Ni, Cu, Fe and Mn in mixed solution B was 1.03:0.2:0.1:0.3:0.4; the molar ratio of Na, Ni, Cu, Fe and Mn in mixed solution C was 1.03:0.1:0.1:0.2:0.6; the mass ratio of mixed solution A, mixed solution B and mixed solution C was 5:4:3;

[0030] The mixed solution A is ionized by an ultrasonic atomizer and then sprayed into a reaction device. During the gradual heating process, the water content of the atomized droplets evaporates to form a solid precipitate, which is further pyrolyzed at 460°C to generate a precursor A. The tail gas in the device after the reaction is completely removed by vacuum pumping, and then nitrogen is introduced into the reaction device to disperse and suspend the precursor A in the device. The mixed solution B is ionized by an ultrasonic atomizer and sprayed into the reaction device to form suspended droplets covering the precursor A. The water content of the droplets evaporates to form a crystalline coating layer, which is further pyrolyzed at 470°C to obtain a two-layer precursor B. The tail gas in the device after the reaction is completely removed by vacuum pumping. Then, nitrogen is introduced into the reaction device to disperse and suspend the two-layer precursor B in the device, and then the mixed solution C is ionized by an ultrasonic sprayer and sprayed into the reaction device to form suspended droplets covering the two-layer precursor B. After the water in the droplets evaporates, a crystalline coating layer is formed on its surface, which is further pyrolyzed at 480°C to obtain a three-layer precursor C; the three-layer precursor C is placed in an atmosphere box furnace, pre-burned at 470°C for 4h, the gap between the rollers is set to 0.5mm, and crushed with a mechanical roller, and then placed in an atmosphere sintering furnace, sintered at 900°C for 12h, and crushed with an air flow mill after sintering to obtain a manganese-based three-layer core-shell structure positive electrode material Na 1.03 Ni 0.23 Cu 0.1 Fe 0.25 Mn 0.42 O2.

[0031] Example 4

[0032] Sodium acetate, nickel acetate, copper acetate, iron acetate and manganese acetate were weighed respectively and dissolved in deionized water, the mass of deionized water being 5 times the sum of the masses of each component, and stirred and heated to 65° C. until completely dissolved to obtain mixed solution A, mixed solution B and mixed solution C, so that the molar ratio of Na, Ni, Cu, Fe and Mn in mixed solution A was 1.03:0.5:0.1:0.2:0.2; the molar ratio of Na, Ni, Cu, Fe and Mn in mixed solution B was 1.03:0.25:0.15:0.3:0.3; the molar ratio of Na, Ni, Cu, Fe and Mn in mixed solution C was 1.03:0.1:0.1:0.2:0.6; the mass ratio of mixed solution A, mixed solution B and mixed solution C was 5:4:3;

[0033] The mixed solution A is ionized by an ultrasonic atomizer and then sprayed into a reaction device. During the gradual heating process, the water content of the atomized droplets evaporates to form a solid precipitate, which is further pyrolyzed at 440°C to generate a precursor A. The tail gas in the device after the reaction is completely removed by vacuum pumping, and then nitrogen is introduced into the reaction device to disperse and suspend the precursor A in the device. The mixed solution B is ionized by an ultrasonic atomizer and sprayed into the reaction device to form suspended droplets covering the precursor A. The water content of the droplets evaporates to form a crystalline coating layer, which is further pyrolyzed at 470°C to obtain a two-layer precursor B. The tail gas in the device after the reaction is completely removed by vacuum pumping. Then, nitrogen is introduced into the reaction device to disperse and suspend the two-layer precursor B in the device, and then the mixed solution C is ionized by an ultrasonic sprayer and sprayed into the reaction device to form suspended droplets covering the two-layer precursor B. After the water in the droplets evaporates, a crystalline coating layer is formed on its surface, which is further pyrolyzed at 500°C to obtain a three-layer precursor C; the three-layer precursor C is placed in an atmosphere box furnace, pre-burned at 550°C for 4h, the gap between the rollers is set to 0.5mm, and crushed with a mechanical roller, and then placed in an atmosphere sintering furnace, sintered at 920°C for 12h, and crushed with an air flow mill after sintering to obtain a manganese-based three-layer core-shell structure positive electrode material Na 1.03 Ni 0.28 Cu 0.12 Fe 0.0.23 Mn 0.37 O2.

[0034] Example 5

[0035] Sodium acetate, nickel acetate, copper acetate, iron acetate and manganese acetate were weighed respectively and dissolved in deionized water, the mass of deionized water being 5 times the sum of the masses of each component, and stirred and heated to 80° C. until completely dissolved to obtain mixed solution A, mixed solution B and mixed solution C, so that the molar ratio of Na, Ni, Cu, Fe and Mn in mixed solution A was 1.03:0.6:0.1:0.15:0.15; the molar ratio of Na, Ni, Cu, Fe and Mn in mixed solution B was 1.03:0.3:0.1:0.3:0.3; the molar ratio of Na, Ni, Cu, Fe and Mn in mixed solution C was 1.03:0.05:0.1:0.15:0.7; the mass ratio of mixed solution A, mixed solution B and mixed solution C was 5:4:3;

[0036] The mixed solution A is ionized by an ultrasonic atomizer and then sprayed into a reaction device. During the gradual heating process, the water content of the atomized droplets evaporates to form a solid precipitate, which is further pyrolyzed at 400°C to generate a precursor A. The tail gas in the device after the reaction is completely removed by vacuum pumping, and then nitrogen is introduced into the reaction device to disperse and suspend the precursor A in the device. The mixed solution B is ionized by an ultrasonic atomizer and sprayed into the reaction device to form suspended droplets covering the precursor A. The water content of the droplets evaporates to form a crystalline coating layer, which is further pyrolyzed at 430°C to obtain a two-layer precursor B. The tail gas in the device after the reaction is completely removed by vacuum pumping. Then, nitrogen is introduced into the reaction device to disperse and suspend the two-layer precursor B in the device, and then the mixed solution C is ionized by an ultrasonic sprayer and sprayed into the reaction device to form suspended droplets covering the two-layer precursor B. After the water in the droplets evaporates, a crystalline coating layer is formed on its surface, which is further pyrolyzed at 460°C to obtain a three-layer precursor C; the three-layer precursor C is placed in an atmosphere box furnace, pre-burned at 500°C for 3h, the gap between the rollers is set to 0.5mm, and crushed with a mechanical roller, and then placed in an atmosphere sintering furnace, sintered at 930°C for 10h, and crushed with an air flow mill after sintering to obtain a manganese-based three-layer core-shell structure positive electrode material Na 1.03 Ni 0.32 Cu 0.1 Fe 0.2 Mn 0.38 O2.

[0037] Example 6

[0038] Sodium acetate, nickel acetate, copper acetate, iron acetate and manganese acetate were weighed respectively and dissolved in deionized water, the mass of deionized water being 5 times the sum of the masses of each component, and stirred and heated to 80° C. until completely dissolved to obtain mixed solution A, mixed solution B and mixed solution C, so that the molar ratio of Na, Ni, Cu, Fe and Mn in mixed solution A was 1.03:0.6:0.2:0.1:0.1; the molar ratio of Na, Ni, Cu, Fe and Mn in mixed solution B was 1.03:0.2:0.2:0.3:0.3; the molar ratio of Na, Ni, Cu, Fe and Mn in mixed solution C was 1.03:0.05:0.15:0.3:0.5; the mass ratio of mixed solution A, mixed solution B and mixed solution C was 5:4:3;

[0039] The mixed solution A is ionized by an ultrasonic atomizer and then sprayed into a reaction device. During the gradual heating process, the water content of the atomized droplets evaporates to form a solid precipitate, which is further pyrolyzed at 420°C to generate a precursor A. The tail gas in the device after the reaction is completely evacuated and then nitrogen is introduced into the reaction device to disperse and suspend the precursor A in the device. The mixed solution B is ionized by an ultrasonic atomizer and sprayed into the reaction device to form suspended droplets covering the precursor A. The water content of the droplets evaporates to form a crystalline coating layer, which is further pyrolyzed at 450°C to obtain a two-layer precursor B. The tail gas in the device after the reaction is completely evacuated and then Then, nitrogen is introduced into the reaction device to disperse and suspend the two-layer precursor B in the device, and then the mixed solution C is ionized by an ultrasonic sprayer and sprayed into the reaction device to form suspended droplets covering the two-layer precursor B. After the water in the droplets evaporates, a crystalline coating layer is formed on its surface, which is further pyrolyzed at 480°C to obtain a three-layer precursor C; the three-layer precursor C is placed in an atmosphere box furnace, pre-sintered at 520°C for 3h, the gap between the rollers is set to 0.5mm, and crushed with a mechanical roller, and then placed in an atmosphere sintering furnace, sintered at 940°C for 8h, and crushed with a jet mill after sintering to obtain a manganese-based three-layer core-shell structure positive electrode material Na 1.03 Ni 0.28 Cu 0.18 Fe 0.24 Mn 0.3 O2.

[0040] Comparative Example 1

[0041] The difference compared with Example 1 is that no gradient structure is synthesized, and the material is obtained by one-time spray pyrolysis by mole.

[0042] Weigh sodium acetate, nickel acetate, copper acetate, iron acetate, and manganese acetate and dissolve them in deionized water, the mass of which is 5 times the sum of the masses of each component. Stir and heat to 75° C. until they are completely dissolved to obtain a mixed solution, wherein the molar ratio of Na, Ni, Cu, Fe, and Mn in the mixed solution is 1.03:0.2:0.1:0.28:0.42:2.

[0043] The mixed solution is ionized by an ultrasonic atomizer and then sprayed into a reaction device. During the gradual heating process, the water in the atomized droplets evaporates to form a solid precipitate, which is further pyrolyzed at 450°C to generate a precursor. The precursor is placed in an atmosphere box furnace, pre-burned at 500°C for 4 hours, the gap between the rollers is set to 0.5mm, and crushed with a mechanical roller. Then, it is placed in an atmosphere sintering furnace and sintered at 900°C for 12 hours. After sintering, it is crushed with a jet mill to obtain a manganese-based three-layer core-shell structure positive electrode material.

[0044] Comparative Example 2

[0045] The difference compared with Example 2 is that no gradient structure is synthesized, and the material is obtained by one-time spray pyrolysis by mole.

[0046] Weigh sodium acetate, nickel acetate, copper acetate, iron acetate, and manganese acetate and dissolve them in deionized water, the mass of which is 5 times the sum of the masses of each component. Stir and heat to 75° C. until they are completely dissolved to obtain a mixed solution, wherein the molar ratio of Na, Ni, Cu, Fe, and Mn in the mixed solution is 1.03:0.23:0.17:0.27:0.33:2.

[0047] The mixed solution was ionized by an ultrasonic atomizer and then sprayed into a reaction device. During the gradual heating process, the water in the atomized droplets evaporated to form a solid precipitate, which was further pyrolyzed at 400°C to generate a precursor. The precursor was placed in an atmosphere box furnace, pre-burned at 450°C for 4 hours, the gap between the rollers was set to 0.5 mm, and crushed with a mechanical roller. Then, it was placed in an atmosphere sintering furnace and sintered at 920°C for 10 hours. After sintering, it was crushed with a jet mill to obtain a manganese-based three-layer core-shell structure positive electrode material.

[0048] Comparative Example 3

[0049] The difference compared with Example 3 is that: no gradient structure is synthesized, and the material is obtained by one-time spray pyrolysis in molar ratio.

[0050] Weigh sodium acetate, nickel acetate, copper acetate, iron acetate, and manganese acetate and dissolve them in deionized water, the mass of which is 5 times the sum of the masses of each component. Stir and heat to 75° C. until they are completely dissolved to obtain a mixed solution, wherein the molar ratio of Na, Ni, Cu, Fe, and Mn in the mixed solution is 1.03:0.23:0.1:0.25:0.42:2.

[0051] The mixed solution is ionized by an ultrasonic atomizer and then sprayed into a reaction device. During the gradual heating process, the water in the atomized droplets evaporates to form a solid precipitate, which is further pyrolyzed at 460°C to generate a precursor. The precursor is placed in an atmosphere box furnace, pre-burned at 470°C for 4 hours, the gap between the rollers is set to 0.5 mm, and crushed with a mechanical roller. Then, it is placed in an atmosphere sintering furnace and sintered at 900°C for 12 hours. After sintering, it is crushed with a jet mill to obtain a manganese-based three-layer core-shell structure positive electrode material.

[0052] Comparative Example 4

[0053] The difference compared with Example 1 is that the spraying order of the mixed solutions A, B and C is opposite.

[0054] Sodium acetate, nickel acetate, copper acetate, iron acetate and manganese acetate were weighed respectively and dissolved in deionized water, the mass of deionized water being 5 times the sum of the masses of each component, and stirred and heated to 70° C. until completely dissolved to obtain mixed solution A, mixed solution B and mixed solution C, so that the molar ratio of Na, Ni, Cu, Fe and Mn in mixed solution A was 1.03:0.3:0.1:0.3:0.3; the molar ratio of Na, Ni, Cu, Fe and Mn in mixed solution B was 1.03:0.2:0.1:0.35:0.35; the molar ratio of Na, Ni, Cu, Fe and Mn in mixed solution C was 1.03:0.1:0.1:0.2:0.6; the mass ratio of mixed solution A, mixed solution B and mixed solution C was 5:4:3;

[0055] The mixed solution C is ionized by an ultrasonic atomizer and then sprayed into a reaction device. During the gradual heating process, the water content of the atomized droplets evaporates to form a solid precipitate, which is further pyrolyzed at 450°C to generate a first precursor. The tail gas in the device after the reaction is completely evacuated and removed. Then, nitrogen is introduced into the reaction device to disperse and suspend the first precursor in the device. The mixed solution B is ionized by an ultrasonic atomizer and sprayed into the reaction device to form suspended droplets covering the first precursor. The water content of the droplets evaporates to form a crystalline coating layer, which is further pyrolyzed at 460°C to obtain a second precursor. The tail gas in the device after the reaction is completely evacuated and removed. The second precursor B is then dispersed and suspended in the device by introducing nitrogen into the reaction device, and the mixed solution A is ionized by an ultrasonic sprayer and sprayed into the reaction device to form suspended droplets covering the second precursor. After the water in the droplets evaporates, a crystalline coating layer is formed on its surface, which is further pyrolyzed at 470°C to obtain a third precursor; the third precursor is placed in an atmosphere box furnace, pre-burned at 500°C for 4h, the gap between the rollers is set to 0.5mm, and crushed with a mechanical roller, and then placed in an atmosphere sintering furnace, sintered at 900°C for 12h, and crushed with an air flow mill after sintering to obtain a manganese-based three-layer core-shell structure positive electrode material Na 1.03 Ni 0.2 Cu 0.1 Fe 0.28 Mn 0.42 O2.

[0056] Performance Testing

[0057] The positive electrode materials prepared in Examples 1-6 and Comparative Examples 1-4 were made into positive electrode sheets, with Celgard 2400 polypropylene microporous membrane as the diaphragm, 1 mol / L NaPF6 mixed organic solvent (EC: DMC: FEC = 4.95: 5: 0.05, volume ratio) as the electrolyte, and a metal sodium sheet as the counter electrode. They were assembled into a button battery of model CR2025 in a glove box filled with argon gas, and the following tests were performed: discharge specific capacity; a button battery test system was used for charge and discharge cycle test, with a charge and discharge voltage range of 2.0-4.0V, the first discharge specific capacity of the battery at a rate of 1C was tested, and then the discharge specific capacity after 100 cycles was tested, and the capacity retention rate was calculated. The results are shown in Table 1:

[0058] Table 1 Performance test results

[0059]

[0060]

[0061] By comparing the above examples and comparative examples, it can be seen that the present invention utilizes a gradient distribution of elements, which reduces the amount of Ni distributed on the surface of the overall particle active material and increases the amount of Ni distributed inside, thereby avoiding the Ni 4+ The problem of reduced cycle performance caused by electrolyte decomposition caused by side reactions with the electrolyte is solved, and at the same time the distribution of the Mn element in the material is changed, effectively improving its capacity performance.

[0062] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be regarded as exemplary and non-limiting from any point of view, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention, and any reference numerals in the claims should not be regarded as limiting the claims involved.

Claims

1. A manganese-based three-layer core-shell structure positive electrode material for sodium ion batteries, characterized in that: It has the following molecular formula: NaNi x Cu y Fe z Mn 1-x-y-z O2, the positive electrode material has a three-layer structure consisting of an inner layer, an intermediate layer and an outer layer, and the stoichiometric ratio of Na, Ni, Cu, Fe and Mn in each layer is 0.5-4:x:y:z:(1-xyz), wherein 0<x≤0.4, 0<y≤0.2, 0<z<0.6; and the content of Ni in each layer decreases from the inside to the outside, and the content of Mn in each layer increases from the inside to the outside; The method for preparing the manganese-based three-layer core-shell structure positive electrode material for sodium ion batteries comprises the following steps: S1: Sodium salt, nickel salt, iron salt, manganese salt and copper salt are weighed and dissolved in deionized water according to different stoichiometric ratios to prepare mixed solutions A, B and C; the content of Ni in the mixed solutions A, B and C decreases gradually, and the content of Mn in the mixed solutions A, B and C increases gradually; S2: ionizing the mixed solution A, spraying it into a reaction device, evaporating and precipitating it, and then pyrolyzing it to generate a precursor A; ionizing the mixed solution B, spraying it into a reaction device, and using a carrier gas to disperse and suspend the precursor A in the reaction device to form a coating layer covering the precursor A, and pyrolyzing it to obtain a two-layer precursor B; ionizing the mixed solution C, spraying it into a reaction device, and using a carrier gas to disperse and suspend the precursor B in the reaction device to form a coating layer covering the precursor B, and pyrolyzing it to obtain a three-layer precursor C; the ionizing device is an ultrasonic atomizer; S3: The three-layer precursor C is pre-sintered, crushed, sintered and then pulverized to obtain a manganese-based three-layer core-shell structure positive electrode material.

2. The manganese-based three-layer core-shell structure positive electrode material for sodium ion battery according to claim 1, characterized in that: In the inner layer, the molar ratio of Na, Ni, Cu, Fe and Mn is 1.03:0.25-0.45:0.05-0.15:0.2-0.4:0.2-0.3; in the middle layer, the molar ratio of Na, Ni, Cu, Fe and Mn is 1.03:0.15-0.25:0.05-0.15:0.2-0.4:0.25-0.4; in the outer layer, the molar ratio of Na, Ni, Cu, Fe and Mn is 1.03:0.05-0.15:0.05-0.15:0.2-0.4:0.45-0.

65.

3. The manganese-based three-layer core-shell structure positive electrode material for sodium ion battery according to claim 1, characterized in that: The sodium salt, nickel salt, iron salt, manganese salt and copper salt are acetates of these metals; the ionization device is an ultrasonic atomizer, and the pyrolysis temperature is 400-600°C.

4. The manganese-based three-layer core-shell structure positive electrode material for sodium ion battery according to claim 1, characterized in that: The mass ratio of mixed solution A, mixed solution B, and mixed solution C is 3-7:2-6:1-5, and the concentration of the solute in mixed solution A, mixed solution B, and mixed solution C is 10-30wt%.

5. The manganese-based three-layer core-shell structure positive electrode material for sodium ion battery according to claim 1, characterized in that: The pre-calcination temperature is 350-500° C. and the pre-calcination time is 4-7 hours.

6. The manganese-based three-layer core-shell structure positive electrode material for sodium ion battery according to claim 1, characterized in that: The crushing device is a double roller machine, and the gap between the double rollers is 0.05-2mm.

7. The manganese-based three-layer core-shell structure positive electrode material for sodium ion battery according to claim 1, characterized in that: The sintering temperature is 700-950° C. and the sintering time is 6-15 hours.

8. A sodium ion battery positive electrode, characterized in that: The battery positive electrode comprises the manganese-based three-layer core-shell structure positive electrode material for sodium ion battery according to claim 1.

Citation Information

Patent Citations

  • Sodium-ion battery positive electrode material, preparation method thereof and sodium-ion battery

    CN108565457A

  • Sodium ion positive electrode material capable of realizing rapid charging and discharging, preparation method of sodium ion positive electrode material and sodium ion battery

    CN115377380A

  • Copper-ion-doped nickel-iron-manganese-based ternary precursor, preparation method and application of copper-ion-doped nickel-iron-manganese-based ternary precursor

    CN115924999A